2021
DOI: 10.5812/jjm.118949
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Genetic Characterization of Vancomycin-resistant and mecC+ Methicillin-resistant Staphylococcus aureus Strains in Clinical Samples of Bojnurd, Northeastern Iran

Abstract: Background: The emergence of antibiotic-resistant Staphylococcus aureus strains is one of the major concerns about the various staphylococcal infections. Vancomycin is one the most important effective antibiotics on staphylococcal lethal infections. To date, vancomycin-resistant strains are increasingly isolated in different parts of the world, and it is alerting. Objectives: The current study was designed to evaluate the prevalence, and antibiotic susceptibility pattern of methicillin-resistant S. aureus (MRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Data obtained from Saudi Arabia showed that ST239 is the most common in Riyadh and Dammam, located in the eastern region of Saudi Arabia [49], while in the western region this clone is not common [50], which is consistent with our findings. All clones identified here have been identified sporadically in the western region by Al-Zahrani et al [51].…”
Section: Antibiotics Testedsupporting
confidence: 59%
See 2 more Smart Citations
“…Data obtained from Saudi Arabia showed that ST239 is the most common in Riyadh and Dammam, located in the eastern region of Saudi Arabia [49], while in the western region this clone is not common [50], which is consistent with our findings. All clones identified here have been identified sporadically in the western region by Al-Zahrani et al [51].…”
Section: Antibiotics Testedsupporting
confidence: 59%
“…Genes responsible for beta-lactam resistance (blaZ, mecA, and mecC) were identified in the studied isolates: the mecA gene was detected in three MRSA isolates (S14, S21, and S23), mecC was identified in S8 and S9 isolates, and blaZ was commonly identified in all isolates except S23 (Table 5). Interestingly, we identified the presence of mecC-MRSA for the first time in our region; mecC is a new divergent from mecA usually associated with animal transmission, and these patients are usually from rural areas [51]. Eight antimicrobial-resistance-associated genes were identified in all of the isolates: the quinolone resistance genes (norA and norC) and their regulators (MgrA for norC and arlS for norA), the major facilitator superfamily MDR efflux pump in S. aureus (LmrS), the multidrug efflux pump (sdrM), the mepA gene which acts as a repressor for multidrug export protein, and the SepA gene that confers resistance to disinfecting agents and dyes [52].…”
Section: Prediction Of Antimicrobial Resistance Mechanism In the Stud...mentioning
confidence: 74%
See 1 more Smart Citation
“…Bacterial co-infections cause higher rates of morbidity and mortality among COVID-19 patients (8). Gram-positive bacteria, especially members of Staphylococcaceae and Streptococcaceae, are among the main causative agents of these co-infections (9).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of mecA, vanA, cfr, and qacA/B genes was evaluated by polymerase chain reaction (PCR) using the primers listed in Table 1, as described previously (8,9).…”
Section: Polymerase Chain Reaction Detection Of Resistance Genesmentioning
confidence: 99%